The Role And Performance Of Baznas In Overcoming Poverty (Case Study Of The Deli Serdang National Amil Zakat Agency) - Adelia Fitra Gustari; Nurhayati Nurhayati (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
This study aims to assess the effectiveness of zakat in alleviating poverty in Deli Serdang. Zakat is allocated to eight categories, including the poor, the destitute, zakat administrators (amil zakat), converts to Islam (mu'allaf), slaves, individuals in debt, those engaged in jihad fi sabilillah, and travelers in need (ibn sabil). Zakat designated for the mustahik (recipients) can be utilized as capital for small-scale businesses, often inaccessible to traditional financial institutions like banks. The process of support includes planning, execution, monitoring, control, and program evaluation, and it is administered by the zakat amil agency as part of their productive zakat initiatives. This initiative aims to stimulate economic activity, enhance the productivity of local businesses, boost income, and ensure sustainability. The research methodology adopted is qualitative and descriptive in nature, focusing on assessing the impact of productive zakat on empowering impoverished communities through a poverty index. The study combines primary data, gathered through surveys, questionnaires, and in-depth interviews with both the program managers at Baznas and the mustahik participating in the community empowerment programs funded by productive zakat. Secondary data is sourced from the BAZNAS Program Report available online, as well as various literature, articles in publications such as magazines, journals, newspapers, and the internet. The research findings indicate that, overall, the mustahik community views the productive zakat program administered by Baznas as highly successful.